Transnational & Immigrant Entrepreneurship in a Globalized World. - Honig, Benson (Rotman-UTP Publishing., 2010)
Transnational and Immigrant Entrepreneurship in a Globalized World brings together leading international scholars from a cross-disciplinary basis to examine the economic, social, regulatory, technological, and theoretical issues related to the impact of transnational entrepreneurs on business and economic development.